Beneficial effects of Dendrobium officinale on metabolic hypertensive rats by triggering the enteric-origin SCFA-GPCR43/41 pathway. Issue 12 (18th May 2021) - Li, Bo; He, Xinglishang; Jin, Hai-Ying; Wang, Hui-Ying; Zhou, Fu-Chen; Zhang, Ning-Yu; Jie, Dong-Ying; Li, Lin-Zi; Su, Jie; Zheng, Xiang; Luo, Rong; Lv, Gui-Yuan; et al.
Abstract : DOFP enhances the production of SCFAs and absorption from the intestines and then activates the SCFA-GPCR43/41 pathway, resulting in improvements in vascular endothelial function and reduction in blood pressure of the ACHSFD-induced MH rats. Abstract : Given the increasing global trend toward unhealthy lifestyles and dietary decisions, such as "over-consumption of alcohol, and high sugar and fat diets" (ACHSFDs), it is not surprising that metabolic hypertension (MH) is now the most common type of hypertension. There is an urgent, global need for effective measures for the prevention and treatment of MH. Improper diet leads to decreased short-chain fatty acid (SCFA) production in the gut, leading to decreased gastrointestinal function, metabolism, and blood pressure as a result of signaling through G-protein-coupled receptors (GPCRs), ultimately causing MH. Previous studies have suggested that Dendrobium officinale (DO) may improve gastrointestinal function, lower blood pressure, and regulate metabolic abnormalities, but it is not clear whether it acts on MH by increasing SCFA and, if so, how. In this research, it was observed that Dendrobium officinale ultrafine powder (DOFP) could lower blood pressure and improve lipid abnormalities in ACHSFD-induced MH model rats. Moreover, DOFP was found to improve the intestinal flora and increased the SCFA level in feces and serum, as well as increased the expressions of GPCR43/41 and eNOS and the nitric oxide (NO) level. An experiment on isolated aorta rings revealed that DOFP improved the vascular endothelial relaxation function in MH rats, and this effect could be blocked by the eNOS inhibitor l -NAME. These experimental results suggest that DOFP improved the intestinal flora and increased the production, transportation, and utilization of SCFA, activated the intestinal-vascular axis SCFA-GPCR43/41 pathway, improved vascular endothelial function, and finally lowered blood pressure in MH model rats. This research provides a new focus for the mechanism of the effect of DOFP against MH by triggering the enteric-origin SCFA-GPCR43/41 pathway.